Molecular portrait of breast cancer in China reveals comprehensive transcriptomic likeness to Caucasian breast cancer and low prevalence of luminal A subtype. (18th March 2015) - Huang, Xiaoyan; Dugo, Matteo; Callari, Maurizio; Sandri, Marco; De Cecco, Loris; Valeri, Barbara; Carcangiu, Maria Luisa; Xue, Jingyan; Bi, Rui; Veneroni, Silvia; Daidone, Maria Grazia; Ménard, Sylvie; et al.
<x xml:space="preserve">Abstract</x> Our analyses of a unique transethnic collection of breast cancer frozen specimens from Shanghai Fudan Cancer Center (Chinese Han) profiled simultaneously with an analogous Caucasian Italian series revealed extensive similarity in the comprehensive taxonomy of transcriptional elements regulating breast cancer biology in Chinese and Caucasian groups. Transcriptional similarity across transethnic cohorts may simplify translational medicine approaches and clinical management of breast cancer patients worldwide. <boxed-text content-type="graphic" id="cam4442-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>